2015
DOI: 10.1016/j.jhep.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Is antenatal screening for hepatitis C virus cost-effective? A decade’s experience at a London centre

Abstract: Background: This study aims to assess the cost-effectiveness of a routine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 29 publications
2
36
0
1
Order By: Relevance
“…To our knowledge, our study is the first to evaluate the cost-effectiveness of HCV screening among pregnant women in the U.S. Our findings conflict with a previous study which found HCV screening among pregnant women in the United States not cost-effective, (42) but that study utilized old interferon-based treatments with low cure rates. Our findings are consistent with a recent study founding antenatal screening in the UK cost-effective with newer interferon-based therapies (43). Our findings are also consistent with studies finding HCV screening in the DAA era cost-effective among a variety of U.S. populations such as adolescents and young adults in primary care settings (35), in prisons (44), in methadone programs (24), and one-time testing strategies in the general population.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, our study is the first to evaluate the cost-effectiveness of HCV screening among pregnant women in the U.S. Our findings conflict with a previous study which found HCV screening among pregnant women in the United States not cost-effective, (42) but that study utilized old interferon-based treatments with low cure rates. Our findings are consistent with a recent study founding antenatal screening in the UK cost-effective with newer interferon-based therapies (43). Our findings are also consistent with studies finding HCV screening in the DAA era cost-effective among a variety of U.S. populations such as adolescents and young adults in primary care settings (35), in prisons (44), in methadone programs (24), and one-time testing strategies in the general population.…”
Section: Discussionsupporting
confidence: 92%
“…The MONARCH (MOdelling the NAtural histoRy and Cost effectiveness of Hepatitis C) model is a previously published and validated HCV disease progression and cost‐effectiveness model designed to progress a cohort of subjects in annual cycles through METAVIR fibrosis stages and potentially end‐stage liver disease (ESLD) complications and death . Patients in METAVIR fibrosis stages F0–F4 incur an annual probability of all‐cause mortality .…”
Section: Methodsmentioning
confidence: 99%
“…Seventeen studies assessed the costs and effects of screening programs and antiviral treatments: seven evaluated screening in general population or subgroup of general population, five in people who inject drugs, four in high‐risk populations and three in other populations . It is to be noted here that two studies evaluated the cost‐effectiveness of HCV screening in more than one population group (general and high‐risk population, and people who inject drugs and high‐risk population).…”
Section: Resultsmentioning
confidence: 99%